Optical rotation quasi-phase-matching for circularly polarized high harmonic generation. - Liu, L; O'Keeffe, K; Hooker, S (2012)
A scheme for quasi-phase-matching high harmonic generation of circularly polarized radiation is proposed: optical rotation quasi-phase-matching (ORQPM). In ORQPM, propagation of the driving radiation in a system exhibiting circular birefringence causes its plane of polarization to rotate; by appropriately matching the period of rotation to the coherence length, it is possible to avoid destructive interference of the generated radiation. It is shown that ORQPM is approximately five times more efficient than conventional QPM, and half as efficient as true phase-matching.